Congenital biliary dilatation in the era of laparoscopic surgery, focusing on the high incidence of anatomical variations of the right hepatic artery. (19th September 2020) - Mori, Yasuhisa; Nakata, Kohei; Aly, Mohammed Y. F.; Ideno, Noboru; Ikenaga, Naoki; Okabe, Yasuhiro; Ishigami, Kousei; Oda, Yoshinao; Nakamura, Masafumi
Abstract: Background: The present study aimed to evaluate anatomical variations of the right hepatic artery (RHA) in patients with congenital biliary dilatation (CBD) and the appropriate approach in laparoscopic surgery for CBD. Methods: The medical records of 36 patients who underwent laparoscopic or open surgery for CBD from 1996 to 2018 were retrospectively reviewed. Radiological evaluation of the origin and course of the RHA in these 36 patients were compared with 195 control patients without CBD. Results: The incidence of the RHA crossing anterior to the common hepatic duct (CHD) was significantly higher in patients with CBD than in those without CBD (33% versus 10%, P = .0001). There was no intraoperative injury of the RHA, irrespective of the course of the RHA. The CHD was divided at the caudal side of the RHA in 11 of 12 patients (92%) with the anterior type of RHA, and in 13 of 24 patients (54%) with the posterior type of RHA ( P = .03). Conclusions: Patients with CBD had a higher incidence of the RHA crossing anterior to the CHD than patients without CBD. Preservation of the RHA in each situation is necessary during surgery for CBD in the era of laparoscopic surgery. Abstract : Highlight Mori and colleagues demonstrated that patients with congenital biliary dilatation had a higher incidence of the right hepatic artery crossing anterior to the common hepatic duct than those without. Preoperative simulation and preservation of the right hepatic artery are necessary during surgery for congenital biliary dilatation in the laparoscopic era.